Production of Biogenic Nanoparticles for the Reduction of 4-Nitrophenol and Oxidative Laccase-Like Reactions - Capeness, Michael J.; Echavarri-Bravo, Virginia; Horsfall, Louise E. (Frontiers in Microbiology, 2019)
Biogenic nanoparticles present a wide range of possibilities for use in industrial applications, their production is greener, they can be manufactured using impure feedstocks, and often have different catalytic abilities compared to their chemically made analogs. Nanoparticles of Ag, Pd, Pt, and the bi-elemental PdPt were produced by Morganella psychrotolerans and Desulfovibrio alaskensis and were shown to be able to reduce 4-nitrophenol, an industrial and toxic pollutant. Nanoparticles were recovered post-reaction and then reused, thus demonstrating continued activity. Biogenic PdNPs were shown to have enhanced specificity in a wide pH activity range in the oxidation of the three common substrates used 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS), 2,6-Dimethoxyphenol and (2,6-DMP) and 3,3′,5,5′-Tetramethylbenzidine (TMB) to determine oxidase-like activity. Overall Pd in a nanoparticle form exhibited higher oxidation activity than its ionic counterpart, highlighting the potential of biogenic nanoparticles over the use of ions or chemically made elemental forms.